PENERAPAN PERMENKEU NO. 09/PMK.03/2021 TENTANG INSENTIF PAJAK UNTUK WAJIB PAJAK TERDAMPAK PANDEMI COVID’19 PADA YAYASAN KASIH KEPRI: bahasa indonesia - Nabela; Vanomy, Afrianti Elsye; lubis, syarif hidayah lubis; hardi bahar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Universal, 2022)
The Indonesian government issued PMK No. 09/PMK.03/2021 at the beginning of 2021 valid until June 2021 and extended again until December 2021, the purpose of the Minister of Finance was passed is to help Taxpayers affected by Covid'19 through PPh 21 DTP Tax incentives (Government Borne Tax) during the Covid-19 Pandemic struck. Many parties have suffered losses as a result of the ongoing pandemic. The results of a survey conducted by the Ministry of Finance in 2021 show that the use of tax incentives is dominated by taxpayers most affected by the pandemic, namely 47% in the trade sector, 19% in the manufacturing sector, and 7% in the construction sector. the rest are other sectors. This Permenkeu is a breath of fresh air that can help employees at the Kasih Kepri Foundation, which is engaged in the world of education as a Taxpayer in income tax incentives (PPh 21). This study aims to find out the application of Minister of Finance Regulation No.09/PMK.03/2021 concerning tax incentives for taxpayers affected by the 2019 Corona Virus Disease pandemic at the Kasih Kepri Foundation. In this study using a qualitative approach with a descriptive study. The method used in this research is a case study. The selection of informants in this study used a purposive sampling technique. The selection of informants for this study are; Head of the Foundation, Head of School and Deputy Head of School. The results of this study indicate that the Kasih Kepri Foundation still needs to conduct outreach to permanent and non-permanent employees in order to increase all employees' understanding of the tax incentives imposed by the Government to support the implementation of PMK No. 09/PMK.03/2021. whereas in terms of implementing the tax administration of the self-assessment system which includes calculations, deposits and reporting of PPH 21 at the Kasih Kepri Foundation, conformity has been found with PMK 09/PMK.03/2021